2008
DOI: 10.1073/pnas.0807507105
|View full text |Cite
|
Sign up to set email alerts
|

Stathmin reveals dissociable roles of the basolateral amygdala in parental and social behaviors

Abstract: Innate parental behaviors and adult social interactions are essential for survival of the individual along with the species as a whole. Because these behaviors require threat assessment of the environment, it is plausible that they are regulated by the amygdalaassociated neural circuitry of fear. However, the amygdala is not a single anatomic and functional unit, and nuclei of the amygdala have multiple inter-and intra-connections. This poses a question as to the exact role of different amygdala nuclei in thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 32 publications
(35 reference statements)
2
46
0
Order By: Relevance
“…Studies have shown that lesioning the basolateral amygdala (BLA) does not hasten maternal responding in nulliparous rats (Numan et al, 1993), and while numerous studies have found that lesioning or inactivating the BLA in pregnant or postpartum rodents and sheep has minor or transient effects on caregiving (Lee et al, 1999, 2000; Martel et al, 2008; Keller et al, 2004b), GABAA receptor antagonism in the BLA and adjacent basomedial nucleus do impair retrieval of pups (Numan et al, 2010). When the BLA does have effects on postpartum maternal behavior, it may do so by receiving sensory inputs from the young and potentiating activity of the mesolimbic system via projections to the nucleus accumbens and ventral palladum (Numan and Stolzenberg, 2009).…”
Section: Neural Basis Of Motheringmentioning
confidence: 99%
“…Studies have shown that lesioning the basolateral amygdala (BLA) does not hasten maternal responding in nulliparous rats (Numan et al, 1993), and while numerous studies have found that lesioning or inactivating the BLA in pregnant or postpartum rodents and sheep has minor or transient effects on caregiving (Lee et al, 1999, 2000; Martel et al, 2008; Keller et al, 2004b), GABAA receptor antagonism in the BLA and adjacent basomedial nucleus do impair retrieval of pups (Numan et al, 2010). When the BLA does have effects on postpartum maternal behavior, it may do so by receiving sensory inputs from the young and potentiating activity of the mesolimbic system via projections to the nucleus accumbens and ventral palladum (Numan and Stolzenberg, 2009).…”
Section: Neural Basis Of Motheringmentioning
confidence: 99%
“…In addition, stathmin knockout mice display enhanced extinction of cued fear conditioning, which was accompanied by an increase in neural activity in the prefrontal cortex and dentate gyrus with a simultaneous decrease in amygdala activity (Martel et al, 2012). Stathmin knockout mice also show an increase in social interactions but a decrease in social recognition memory and affiliative maternal care, which were associated with stathmin expression in the basolateral amygdala (Martel et al, 2008). Stathmin transgenic mice expressing Stat4A, an unphosphorylatable stathmin mutant, show reduced contextual fear memory (Uchida et al, 2014), suggesting that stathmin phosphorylation plays an important role in brain function.…”
Section: Role Of Stathmin In Synaptic Plasticity and Behaviormentioning
confidence: 99%
“…Thus, it is not surprising that growing evidence links dysfunction in the adult brain to stathmin and microtubules. Stathmin has been implicated in abnormal states of fear, anxiety, cognition, social behavior, and brain trauma in rodents and humans (Brocke et al, 2010; Ehlis et al, 2011; Elder et al, 2012; Martel et al, 2012; Martel et al, 2008; Shumyatsky et al, 2005), suggesting microtubule involvement in these processes. Common single nucleotide polymorphisms (SNPs) in the STMN1 gene significantly impacted fear and anxiety responses in humans, measured with the startle and cortisol stress response (Brocke et al, 2010).…”
Section: Implication Of Stathmin and Microtubule In Neuropsychiatmentioning
confidence: 99%
“…In mammals, it is known that amygdala enriched stathmin is required for the expression of innate fear and the formation of memory for learned fear [67][68][69]. Interestingly, Ov-stm undergoes in the octopus to a negative regulation in response to fear conditioning.…”
Section: Criterion Judgement Notesmentioning
confidence: 97%